+0  
 
0
278
1
avatar+272 

 1.  Let f(a,b) = 2a - 3b^2 + 7. If f(b,3) = 90, then what is b?

 

2.  Suppose a(x) = 3x - 7 and b(x) = 2 - x^3. Find a(b(3)) - b(a(3)).

 

Thanks :D

WhichWitchIsWhich  Nov 4, 2017

Best Answer 

 #1
avatar+6979 
+2

1)

f(b,3) = 2b - 3(3)^2 + 7  = 2b - 20

 

2b - 20 = 90

2b = 110

b = 55

 

2)

b(3) = 2 - 3^3 = -25

a(3) = 3(3) - 7 = 2

 

a(b(3)) - b(a(3))

= a(-25) - b(2)

= 3(-25) - 7 - (2 - 2^3)

= -75 - 7 + 6

= -76

MaxWong  Nov 4, 2017
 #1
avatar+6979 
+2
Best Answer

1)

f(b,3) = 2b - 3(3)^2 + 7  = 2b - 20

 

2b - 20 = 90

2b = 110

b = 55

 

2)

b(3) = 2 - 3^3 = -25

a(3) = 3(3) - 7 = 2

 

a(b(3)) - b(a(3))

= a(-25) - b(2)

= 3(-25) - 7 - (2 - 2^3)

= -75 - 7 + 6

= -76

MaxWong  Nov 4, 2017

3 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.